Sądy, sędziowie, sykofanci w Acharnejczykach Arystofanesa - Szefliński, Waldemar (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
Szefliński Waldemar, Sądy, sędziowie i sykofanci w „Acharnejczykach” Arystofanesa (Courts, judges, and sycophants in Aristophanes’ Acharnians). The article is a voice in the discussion on the reception of Aristophanic comedies. Through a detailed analysis of all the court-related aspects of the Acharnians (lexicon pertaining to legal issues, court accessories, individuals involved in court proceedings as well as court-related onymy), it is argued that the comedy, traditionally viewed as an anti-war text, can also be included into the body of Aristophanes’ comedies that satirize various aspect of the Athenian juridical reality of the 5th century BCE.